2019
DOI: 10.15282/ijleal.v9.308
|View full text |Cite
|
Sign up to set email alerts
|

Integrasi Elemen Kemahiran Berfikir Aras Tinggi (KBAT) Berasaskan Kit Media dalam Amalan Pembelajaran dan Pemudahcaraan Guru Pelatih Bahasa Arab

Abstract: Kajian ini bertujuan untuk menganalisis integrasi antara elemen Kemahiran Berfikir Aras Tinggi (KBAT) dan instrumen kit media dalam amalan pembelajaran dan pemudahcaraan (PdPc) guru-guru pelatih bahasa Arab UPSI. Ia melibatkan dua peringkat. Peringkat pertama merekabentuk dan mengolah kit media yang mempunyai elemen KBAT oleh guru pelatih bahasa Arab. Manakala peringkat kedua pula menganalisis keberkesanan penggunaan kit media ini sebagai satu medium efisyen dan praktikal untuk digunakan sepanjang sesi latihan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…This in line with the findings from the study by Nur Hawa Hanis and Ghazali (2018) involving 143 History trained teachers in Perak, where a positive attitude towards the implementation of HOTS was observed. Moreover, Saipolbahrin et al (2019) also found that pre-service teachers were always positive towards the implementation of HOTS in school. All teachers should have a positive attitude if the implementation of HOTS is to be realized in school, since the negative attitude diminishes efforts and causes confusion in implementing HOTS (Munawaroh et al, 2018).…”
Section: Discussionmentioning
confidence: 83%
“…This in line with the findings from the study by Nur Hawa Hanis and Ghazali (2018) involving 143 History trained teachers in Perak, where a positive attitude towards the implementation of HOTS was observed. Moreover, Saipolbahrin et al (2019) also found that pre-service teachers were always positive towards the implementation of HOTS in school. All teachers should have a positive attitude if the implementation of HOTS is to be realized in school, since the negative attitude diminishes efforts and causes confusion in implementing HOTS (Munawaroh et al, 2018).…”
Section: Discussionmentioning
confidence: 83%